Calculation of reinforced concrete structures under conditions of flat stressed state - Богдан, С. Ю. (Proceedings of National Aviation University (archive), 2002)
The approach to the estimation of the boundary condition of reinforced concrete structures under conditions of a plane stressed state based on the method of fracture mechanics is proposed. The graphic interpretation of the method and scheme of the deformed state of the reinforced concrete panel is given. An example of determining the bearing capacity of a beam-wall with a rectangular cut-out for two dangerous sections is considered